Spiders of Sabah: Fifty new records including the description of a new Leucauge species - Dzulhelmi Muhammad Nasir; Wong Chun Xing; Asraf Bakri; Norma-Rashid Yusoff; Faszly Rahim (Society for Indonesian Biodiversity, 2024)
Non-Indexed Publication